Creating digital collections - Liu, Shu, 1978-, author; Hunter, Nancy Chaffin, author; Oehlerts, Beth F., author (Colorado State University. Libraries, 2009)
Presented at the Inaugural Conference on German-Russian Studies, June 26, 2009 at Colorado State University Libraries, Fort Collins, Colorado.
Keywords: Colorado State University. Libraries; metadata; web access; digital repositories; digital collections; digitization; project management